Corporate effects and dynamic managerial capabilities - Adner, Ron; Helfat, Constance E. (Strategic Management Journal, 2003)
Abstract Corporate effects in variance decomposition capture heterogeneity of business performance derived from factors internal to firms at the corporate level. Most estimates of corporate effects do not include effects associated with fluctuations in returns over time, except insofar as the fluctuations affect the average corporate return for the time period in question. Exclusion of the time‐varying dimension of the corporate effect makes it difficult to fully understand the effect of corporate strategy and the actions of corporate managers, particularly in response to a changing environment. The evidence in this article shows that within a single industry, where managers face the same external environment, time‐varying corporate effects associated with corporate level managerial decisions are statistically significant. We introduce the concept of dynamic managerial capabilities to underpin the finding of heterogeneity in managerial decisions and firm performance in the face of changing external conditions. Copyright © 2003 John Wiley & Sons, Ltd.